The 300 Mt Windy Craggy Besshi-Type Massive Sulfide Deposit, Northwestern British Columbia, Canada: An Analog For Modern Seafloor Sulfide Deposits At Sedimented Settings? - Jan M. Peter (International Marine Minerals Society, 1993)
The Early Norian Windy Craggy massive sulfide deposit is within the allochthonous Alexander terrane of the Insular tectonic belt in extreme northwestern British Columbia (Figure 1). Host rocks are the Middle Tats Volcanics, part of an informally-named volcano-sedimentary succession of mixed graphitic argillites and mafic pillowed and massive volcanic flows and sills of Upper Triassic age (Figure 2) that have suffered only lower greeschist-facies metamorphism. The volcanic rocks are light rare earth element (LREE)-enriched and display a variably developed back-arc subduction signature. Major and trace element compositions of the host argillite show that it contains an appreciable hydrothermal component, as evidenced by low high Fe and Mn contents. These sediments therefore record steady, continuous hydrothermal activity punctuated by intermittent turbidity currents sweeping into the basin. The deposit consists of at least two discrete sulfide lenses (the North and South Sulfide Bodies), as shown in Figure 3, a level plan at the elevation of the exploration workings. Published reserves at 0.5% copper cut-off are 297.4 million tonnes grading 1.38% Cu, 0.08% Co, 0.21 g/t Au and 3.9 g/t Ag (as of December 1991). However, the deposit is larger than this and further drilling is required to delineate it completely. Mineralization comprises massive sulfide, stringer/stockwork, and finely bedded to laminated sulfides and exhalites. Stockwork mineralization consists of sulfide-quartz-chlorite veins with attendant chlorite and silica alteration. Mineralization consists predominantly of massive pyrrhotite andlor pyrite with lesser chalcopyrite and magnetite. Figure 4 is an oblique section through the North Sulfide Body, the most northerly sulfide mass shown in Figure 3, which shows the distribution of the pyrite and pynhotite-rich massive mineralization and the stringer zone. The North Sulfide Body contains appreciable sphalerite, whereas the South Sulfide Body contains only trace amounts. Gangue minerals include quartz, chlorite, calcite, siderite, ankerite, stilpnomelane and magnetite. The minor hydrothermal exhalite sediments are comprised of chert, carbonate, and minor